Australian LGBTQ teachers, exclusionary spaces and points of interruption. (March 2016) - Gray, Emily M; Harris, Anne; Jones, Tiffany
Lesbian, gay, bisexual, transgender and queer (LGBTQ) teachers are a marginalised group that historically have been absent from research on sexuality and schooling. Rather, much research in the field has focused upon the experiences of same sex attracted and increasingly, gender diverse young people in schools, as well as the delivery of sexuality education. Up until recently, very little research has been carried out that explicitly addresses the experiences of LGBTQ teachers, particularly within the Australian context. This article focuses upon key issues arising from the semi-structured interviews that the Out/In Front team carried out as part of a pilot study that took place between April and July 2013 in the state of Victoria, Australia. We interviewed nine current or former teachers working within primary and secondary education across the public, Catholic and private sectors. This paper focuses upon the notion that LGBTQ teachers exist within a 'space of exclusion' that is dominated by discursive mechanisms that (re)produce heteronormativity. We also argue that the Victorian policy context – as well as increasing socio-political tolerance for LGBTQ people within Australia – enables LGBT teachers to interrupt the discursive frameworks within which their professional lives are situated.